2009
DOI: 10.1100/tsw.2009.132
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Toxic Metals in Indian Smokeless Tobacco Products

Abstract: This study targets the lesser-known ingredients of smokeless tobacco products, i.e., the toxic metals, in Indian brands. The metals selected in the study included lead (Pb), cadmium (Cd), arsenic (As), copper (Cu), mercury (Hg), and selenium (Se). The differential pulse anodic stripping voltammetry (DPASV) technique was used for estimating the metals Pb, Cd, and Cu; square wave voltammetry for As; and the cold vapor atomic absorption technique for Hg. The resulting levels of the metals were compared to the dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…[15] In a study of seven Indian SLT products, high level of copper were detected in four gutka products as compared to zarda, creamy snuff, and khaini, which do not contain areca nut. [16] Jacob et al, [17] demonstrated a definitive dose-dependent relationship between the frequency and duration of chewing areca nut without tobacco and the development of OSF in users.…”
Section: Common Ingredients Present In Various Slt Products/preparationsmentioning
confidence: 98%
“…[15] In a study of seven Indian SLT products, high level of copper were detected in four gutka products as compared to zarda, creamy snuff, and khaini, which do not contain areca nut. [16] Jacob et al, [17] demonstrated a definitive dose-dependent relationship between the frequency and duration of chewing areca nut without tobacco and the development of OSF in users.…”
Section: Common Ingredients Present In Various Slt Products/preparationsmentioning
confidence: 98%
“…Though the actual levels of these compounds in the products tested were not given in this report, in another laboratory study on the chemical composition of several common brands of pan masala, it was found that most of them were adulterated with PAH, certain insecticides such as DDT and BHC isomers, in addition to toxic metals such as copper, zinc and magnesium (all these are known to possess carcinogenic, tumorigenic, teratogenic and mutagenic potentials), in higher concentrations than permissible limits [51] . High concentrations of toxic metals such as lead, arsenic, cadmium and copper, much above the permissible limits prescribed by the WHO, were also detected in several Indian brands of tobacco blended pan masala [65] . Several dangerous volatile aldehydes, such as formaldehyde, acrolein, crotonaldehyde, propionaldehyde and isobutyraldehyde have also been detected in the studies conducted on the chemical analysis of pan masala in the Cancer Research Institute of Tata Memorial Centre, Mumbai, India [64] .…”
Section: Adulteration In Pan Masalamentioning
confidence: 99%
“…In a market known for its diversity of tobacco products, smokeless tobacco in India remains by far the most prevalent form used (26%), followed by bidis (a filterless cigarette-like product with 9% prevalence) and cigarettes (6% prevalence). (India Ministry of Health and Family Welfare (2010)) Though there are many forms of smokeless tobacco products in India, they tend to share a level of toxicity that is considerably higher than that of smokeless products in Western markets (Prabhakar et al, 2013;Dhaware et al, 2009). ST use in India is linked to oral and digestive tract cancers, which are the top two causes of cancer mortality among men in India, and to reproductive effects among women (Dikshit et al, 2012;Gupta and Ray, 2003).…”
Section: Introductionmentioning
confidence: 97%